Substance Abuse Treatment, HIV/AIDS, and the Continuum of Response for People Who Inject Drugs. (29th November 2012) - Kresina, Thomas F.; Lubran, Robert; Clark, H. Westley; Cheever, Laura W.
Abstract : The continuum of response (CoR) to HIV/AIDS is a framework for implementation of HIV prevention, care, and treatment programs based on a national strategic plan for HIV/AIDS services. The CoR for people who inject drugs (PWID) is an important extension of the developed CoR to HIV/AIDS. The CoR-PWID employs stakeholders who together plan, develop, pilot, and provide a full range of services that address the various prevention, care/support, and treatment needs of people, families, and communities infected or affected by HIV/AIDS and injection drug use. The CoR-PWID comprises a broad range of services that include but are not limited to the World Health Organization priority interventions for HIV/AIDS prevention, treatment, and care in the health sector and the package of essential interventions for the prevention, treatment, and care of HIV for people who inject drugs. Implementation of these well-defined, essential prevention, care/support, and treatment services, in addition to locally defined needed services, in a coordinated fashion is important to clients, their families, and communities. The CoR-PWID is, therefore, a necessary framework essential for service development for countries that address HIV/AIDS in populations of PWID.